Senegal : Sixth Review Under the Policy Support Instrument, Request for a Three-Year Policy Support Instrument and Cancellation of Current Policy Support Instrument-Staff Report; Debt Sustainability Analysis; Press Release; Executive Director Statement. (IMF Staff Country Reports; Country Report ;, 2010)
The economy has started to recover from a slowdown associated with the global financial crisis. Senegal has made significant progress under a three-year Policy Support Instrument (PSI), but challenges remain. Increasing growth and reducing vulnerabilities and poverty require broad-based reforms. Higher revenues and better spending quality are essential to creating more fiscal space for priority spending, including infrastructure spending. To help address growth bottlenecks, higher infrastructure investment will temporarily raise fiscal deficits. The contributions of the financial sector and the energy sector to growth should be enhanced.